LAMINATE, METHOD FOR PRODUCING LAMINATE, THERMOELECTRIC CONVERSION ELEMENT, AND MAGNETIC SENSOR
By preparing a polycrystalline Co-based Heusler alloy thin film on a non-single crystal and flexible substrate, combining AlN buffering and cap layer, the manufacturing problem of magnetic materials on a non-single crystal substrate is solved, and efficient thermoelectric conversion and magnetic sensing are achieved.
Patent Information
- Application Number
- JP2021028690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-25
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2041-02-25
AI Technical Summary
The existing magnetic materials are difficult to manufacture on non-single crystal substrates or flexible substrates, and their thermoelectric conversion efficiency is not high enough.
Using polycrystalline Co-based Heusler alloy film material, by depositing an AlN buffer layer and an AlN cap layer on the substrate, combined with a heat treatment process, the crystal orientation of the alloy is oriented in the film thickness direction to form a multi-layer structure.
High-efficiency thermoelectric conversion and magnetic sensing on non-single crystal and flexible substrates are achieved, and the deformation capability and thermoelectric conversion efficiency of the material are improved.
Smart Images

Figure 0007628700000001 
Figure 0007628700000002 
Figure 0007628700000003
Abstract
Description
[Technical field]
[0001] The present invention ,product The present invention relates to a method for producing a layered body and a laminated body, as well as a thermoelectric conversion element and a magnetic sensor. [Background technology]
[0002] Patent Document 1 describes a thermoelectric conversion device that includes a thermoelectric conversion element made of an antiferromagnetic material having a non-collinear spin structure, and the thermoelectric conversion element generates a voltage due to a temperature difference that occurs in a direction perpendicular to the in-plane micromagnetization direction due to the anomalous Nernst effect.
[0003] Patent Document 2 describes a thermoelectric conversion element that is made of a material with a band structure having a Weyl point in the vicinity of the Fermi energy and has a thermoelectric mechanism that generates an electromotive force by the anomalous Nernst effect. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6611167 [Patent Document 2] International Publication No. 2019 / 009308 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the magnetic materials described in Patent Documents 1 and 2 are single crystal bulk samples or single crystal thin film samples. Therefore, there is a problem that it is difficult to fabricate the magnetic material on a non-single crystal substrate or a flexible substrate. In addition, if the magnetic material is not single crystal, there is a problem that the thermoelectric conversion efficiency is insufficient.
[0006] The present invention has been made in consideration of the above problems, and aims to provide a magnetic material, a laminate, and a method for manufacturing the laminate that can be fabricated on a non-single crystal substrate or a flexible substrate and have excellent thermoelectric conversion efficiency, as well as a thermoelectric conversion element and a magnetic sensor that have the laminate. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides the following means. (1) One embodiment of the magnetic material according to the present invention has a polycrystalline Co-based Heusler alloy and is in the form of a film, The crystal structure of the Co-based Heusler alloy is at least one selected from the group consisting of an L21 ordered structure and a B2 structure, The Co-based Heusler alloy is characterized in that its crystal orientation is oriented in the thickness direction of the film. (2) The magnetic material described in (1) has a chemical composition represented by the formula: Co α Mn β X γ It is expressed as X is at least one selected from the group consisting of Ga, Al, Si, and Ge; α may be in the range of 1.8 to 2.2, β may be in the range of 0.8 to 1.2, and γ may be in the range of 0.8 to 1.2. (3) In the magnetic material according to (1) or (2), the half-width of an X-ray diffraction peak of the crystal orientation of the Co-based Heusler alloy oriented in the thickness direction of the film may be 1° or less. (4) In the magnetic material according to any one of (1) to (3), the film may have a thickness of 2 nm or more and 50 nm or less. (5) One embodiment of the laminate according to the present invention comprises a substrate and a buffer layer provided on the substrate, the buffer layer containing AlN, the crystal structure of the AlN being at least one selected from the group consisting of cubic and hexagonal crystals; The buffer layer is provided on the buffer layer, and the buffer layer is provided on the buffer layer from a side closer to the buffer layer. An alloy layer containing the magnetic material according to any one of claims 1 to 4; The present invention is characterized in that it comprises a cap layer having AlN, the crystal structure of which is at least one type selected from the group consisting of cubic and hexagonal crystals, and a mixed layer having the cap layer. (6) The laminate according to (5) may further include one or more mixed layers on the mixed layer. (7) In the laminate according to (5) or (6), the buffer layer may have a thickness of 10 nm or more and 50 nm or less, and the cap layer may have a thickness of 1 nm or more and 50 nm or less. (8) One aspect of a thermoelectric conversion element according to the present invention is characterized by comprising a thermoelectric conversion material having the laminate according to any one of (5) to (7) above, and an electrode material. (9) One aspect of the magnetic sensor according to the present invention is characterized in that it has a detection unit for detecting magnetism, the detection unit including the laminate according to any one of (5) to (7). (10) One embodiment of the method for producing a laminate according to the present invention is a method for producing a laminate according to any one of (5) to (7), comprising the steps of: providing an AlN layer on a substrate; providing an alloy layer having a Co-based Heusler alloy on the AlN layer; providing a cap layer comprising AlN on the alloy layer; and heat treating the base material on which the cap layer is provided at a temperature of 400° C. or more and 800° C. or less. (11) In the method for producing a laminate according to (10), in the heat treatment step, the pressure is 10 -4 Pa or less, and the heat treatment time may be 2 hours or more. Effect of the Invention
[0008] According to the present invention, it is possible to provide a magnetic material, a laminate, and a method for manufacturing the laminate, which can be fabricated on a non-single crystal substrate or a flexible substrate and have excellent thermoelectric conversion efficiency, as well as a thermoelectric conversion element and a magnetic sensor having the laminate. [Brief description of the drawings]
[0009] [Figure 1]1 is a schematic diagram of a laminate according to an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of the L21 ordered structure and electronic structure of a Co-based Heusler alloy. [Diagram 3] 1 is a schematic diagram of a thermoelectric conversion element according to an embodiment of the present invention. [Figure 4] 1 is a schematic diagram showing a magnetic sensor according to an embodiment of the present invention; [Diagram 5] 2 is a flowchart of a method for manufacturing a laminate according to an embodiment of the present invention. [Figure 6] 1 is a TEM photograph of a laminate according to an embodiment of the present invention. [Figure 7] 1 shows the results of X-ray diffraction measurement of a laminate according to an embodiment of the present invention. [Figure 8] 4 shows the results of measuring the X-ray reflectance of a laminate according to an example of the present invention. [Figure 9] 1 shows the measurement results of the anomalous Nernst effect of a laminate according to an embodiment of the present invention. [Figure 10] 1 shows the measurement results of the anomalous Hall effect of a stack according to an embodiment of the present invention. [Figure 11] 1 is a TEM photograph of a laminate according to an embodiment of the present invention. [Figure 12] FIG. 13 is a diagram showing the measurement results of the anomalous Nernst voltage when the magnetic material according to the embodiment of the present invention is formed on a flexible substrate. [Figure 13] 1 is a photograph of a laminate in which a magnetic material according to an embodiment of the present invention is formed on a polyimide substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Magnetic materials> First, a magnetic material according to an embodiment of the present invention will be described. The magnetic material according to an embodiment of the present invention has a polycrystalline Co-based Heusler alloy. The crystal structure of the Co-based Heusler alloy is at least one type selected from the group consisting of an L21 ordered structure and a B2 structure. The magnetic material according to an embodiment of the present invention is in the form of a film. The crystal orientation of the Co-based Heusler alloy is oriented in the thickness direction of the film. An example of the film shape is a thin film.
[0011] (Co-based Heusler alloy) In this embodiment, the magnetic material is a polycrystalline Co-based Heusler alloy. The chemical composition of the Co-based Heusler alloy is represented by the formula: α Mn β X γ It is preferable that the formula is represented by the formula: where X is at least one of the group consisting of Ga, Al, Si, and Ge. It is preferable that α is in the range of 1.8 to 2.2, β is in the range of 0.8 to 1.2, and γ is in the range of 0.8 to 1.2. This further improves the thermoelectric conversion efficiency of the magnetic material and the sensitivity of the magnetic sensor. The Co-based Heusler alloy is polycrystalline. This improves the deformability of the magnetic material. The chemical composition of the magnetic material may be measured by, for example, energy dispersive X-ray spectroscopy (EDS). The deformability indicates the magnitude of the deformation amount of the macro film in the elastic region. If the deformability is large, it indicates that a larger deformation is allowed in the elastic region. Also, if the deformability is small, it indicates that the amount of deformation allowed in the elastic region is small.
[0012] (Crystal structure of Co-based Heusler alloy) In this embodiment, the crystal structure of the Co-based Heusler alloy is at least one of the group consisting of the L21 ordered structure and the B2 structure. This further improves the thermoelectric conversion efficiency of the magnetic material. FIG. 2 is a schematic diagram of the L21 ordered structure of the Co-based Heusler alloy (source: Patent Document 2). As shown in FIG. 2, the L21 structure is a structure in which four face-centered lattices are nested. If the four sublattices are A, B, C, and D, the fractional coordinates are expressed as (0, 0, 0), (1 / 4, 1 / 4, 1 / 4), (1 / 2, 1 / 2, 1 / 2), and (3 / 4, 3 / 4, 3 / 4), respectively. In the L21 ordered structure, U atoms occupy the A and C sites, V atoms occupy the B site, and W atoms occupy the D site. In FIG. 2, the U atoms are Co, the V atoms are Ga, and the W atoms are Mn. In the L21 ordered structure, the V atoms and the W atoms may be completely interchanged. In the B2 structure, the arrangement of V and W atoms occupying the B and D sites is disordered. In this embodiment, the crystal structure of the Co-based Heusler alloy is preferably an L21 ordered structure. This further improves the thermoelectric conversion efficiency of the magnetic material and the sensitivity of the magnetic sensor.
[0013] (membrane shape) In this embodiment, the magnetic material is in a film shape. This improves the deformability of the magnetic material. The thickness of the film is preferably 2 nm or more and 50 nm or less. When the thickness of the film is 2 nm or more, the thermoelectric conversion efficiency of the magnetic material and the sensitivity of the magnetic sensor are further improved. The thickness of the film is preferably 5 nm or more, more preferably 8 nm or more, and even more preferably 10 nm or more. When the thickness of the film is 50 nm or less, the bending properties of the magnetic material are further improved. The thickness of the film is preferably 40 nm or less, more preferably 30 nm or less, and even more preferably 25 nm or less.
[0014] (Crystal orientation) In this embodiment, the crystal orientation of the Co-based Heusler alloy is oriented in the thickness direction of the film. This improves the thermoelectric conversion efficiency of the magnetic material. The crystal orientation of the Co-based Heusler alloy is oriented in the thickness direction of the film, meaning that the same crystal plane is observed when the magnetic material is viewed from a direction parallel to the thickness direction of the film. It is preferable that the half-width of the X-ray diffraction peak of the crystal orientation of the Co-based Heusler alloy oriented in the thickness direction of the film is 1° or less. This allows the crystal orientation of the Co-based Heusler alloy to be oriented higher in the thickness direction of the film. In addition, the crystallinity of the Co-based Heusler alloy is further improved. As a result, the thermoelectric conversion efficiency of the magnetic material and the sensitivity of the magnetic sensor are further improved. The crystal orientation of the Co-based Heusler alloy oriented in the thickness direction of the film may be a (110) plane. In addition, in this embodiment, since the magnetic material is polycrystalline, each crystal grain has a crystal grain obtained by rotating an arbitrary crystal grain around an axis in the thickness direction of the film.
[0015] Here, the half-width of the X-ray diffraction peak is the half-width of the X-ray diffraction peak obtained by measuring a plane perpendicular to the thickness direction of the film by X-ray diffraction. The X-ray diffraction method can be a known method.
[0016] The magnetic material according to this embodiment has the above-mentioned configuration. Next, the effects of the magnetic material according to this embodiment will be described. Co-based Heusler alloys exhibit a large anomalous Nernst effect (ANE) and anomalous Hall effect (AHE). For this reason, they have attracted attention as a candidate material for high-sensitivity sensors and high-efficiency thermoelectric conversion elements.
[0017] The reason why Co-based Heusler alloys show a large anomalous Nernst effect is that they have a unique electronic structure topology. As shown in Figure 3, Co2MnGa has a Fermi energy E F In the vicinity of the Fermi surface, the band that forms the largest Fermi surface intersects with another band, forming a linear dispersion. Since the dispersion of both bands is almost flat, the density of states (DOS) becomes large. α Mn βX γ Since it has a topological electronic structure as shown in Figure 4, it is thought to show a large anomalous Nernst effect.
[0018] Anomalous Nernst coefficient S ANE is thought to be expressed by the following equation (1). S ANE =ρ xx α xy -S SE ×tan θ AHE (1) Where, ρ xx is the longitudinal resistivity, α xy is the transverse thermoelectric conductivity, S SE is the Seebeck coefficient, θ AHE is the anomalous Hall angle.
[0019] As shown in equation (1), as the anomalous Hall coefficient increases, the anomalous Nernst coefficient also tends to increase. Therefore, it is believed that materials with a large anomalous Nernst coefficient often exhibit a large anomalous Hall coefficient.
[0020] In order to realize the above-mentioned excellent properties, bulk materials grown as single crystals and single crystal thin films grown on single crystal substrates have been produced. However, the bulk materials grown as single crystals and the single crystal thin films grown on single crystal substrates have insufficient deformability, making it difficult to deform them into various shapes. For this reason, it has been difficult to apply Co-based Heusler alloys to practical devices.
[0021] Since the magnetic material according to this embodiment is polycrystalline, it can be fabricated on a non-single crystal substrate or a flexible substrate. Therefore, the magnetic material according to this embodiment has higher deformability than bulk materials grown as single crystals and single crystal thin films grown on single crystal substrates. In addition, the magnetic material according to this embodiment has a large anomalous Nernst effect (ANE) and anomalous Hall effect (AHE) because the crystal orientation of the Co-based Heusler alloy is oriented in the thickness direction of the film. Therefore, the magnetic material according to this embodiment has high thermoelectric conversion efficiency and high magnetic sensitivity.
[0022] Next, a laminate 10 according to an embodiment of the present invention will be described with reference to the drawings. Note that, in cases where the same configuration is used, the same reference numerals will be used and the description will be omitted.
[0023] <Laminate 10> Fig. 1 is a schematic diagram of a laminate 10 according to an embodiment of the present invention. As shown in Fig. 1, the laminate 10 according to this embodiment includes a substrate 20, a buffer layer 30, a mixed layer 40a, and a mixed layer 40b. The mixed layer 40a includes an alloy layer 41a and a cap layer 42a. The mixed layer 40b includes an alloy layer 41b and a cap layer 42b.
[0024] The buffer layer 30 is provided on the substrate 20. The mixed layer 40a is provided on the buffer layer 30. The mixed layer 40b is provided on the mixed layer 40a.
[0025] (Base material 20) As shown in FIG. 1, the substrate 20 is a base of the laminate 10. The substrate 20 is made of a heat-resistant material. The substrate 20 is preferably heat-resistant at 200° C. or higher. This further promotes ordering of the Co-based Heusler alloy layer into the L21 structure. The substrate 20 may be, for example, an inorganic material or an organic material having heat resistance. Examples of the substrate 20 include thermally oxidized Si, Al2O3, SiO2, glass, and polyimide. The substrate 20 is preferably deformable. This further improves the deformability of the laminate. The thickness of the substrate 20 is not particularly limited, but may be, for example, a lower limit of 50 nm or more. Also, the upper limit may be, for example, 1 mm. When the substrate 20 is a material having a crystalline structure, the substrate 20 may be polycrystalline. The substrate may be a non-single crystal substrate or a flexible substrate.
[0026] (Buffer layer 30) As shown in FIG. 1, the buffer layer 30 is provided on the substrate 20. In this embodiment, the buffer layer 30 contains AlN. The crystal structure of AlN is at least one of a group consisting of a cubic crystal and a hexagonal crystal. This allows the crystal orientation of the alloy layer 41a to be appropriately oriented. In addition, the alloy layer 41a can have a polycrystalline structure. This allows the deformability of the laminate 10 to be improved.
[0027] The buffer layer 30 is disposed between the substrate 20 and the alloy layer 41a, thereby improving the crystallinity of the alloy layer 41a. As a result, crystal defects other than those at grain boundaries in the alloy layer 41a can be reduced. As a result, the thermoelectric conversion efficiency of the laminate 10 and the sensitivity of the magnetic sensor can be improved.
[0028] In this embodiment, the thickness of the buffer layer 30 is preferably 10 nm or more and 50 nm or less. When the thickness of the buffer layer 30 is 10 nm or more, the crystallinity of the alloy layer 41a can be further improved. This can further improve the thermoelectric conversion efficiency of the laminate 10 and the sensitivity of the magnetic sensor. The thickness of the buffer layer 30 is more preferably 18 nm or more. On the other hand, when the thickness of the buffer layer 30 is 50 nm or less, the thickness of the laminate 10 is reduced, and the bending deformability is further improved. The thickness of the buffer layer 30 is more preferably 30 nm or less.
[0029] (Mixed layer 40a) As shown in FIG. 1, the mixed layer 40a is provided on the buffer layer 30. The mixed layer 40a has an alloy layer 41a and a cap layer 42a from the side closer to the buffer layer. The alloy layer 41a has the magnetic material according to the embodiment of the present invention. This improves the deformability of the laminate 10. In addition, the thermoelectric conversion efficiency of the laminate 10 and the sensitivity of the magnetic sensor are improved. The effect and the preferred configuration of the alloy layer 41a are the same as those of the magnetic material according to the embodiment of the present invention.
[0030] In this embodiment, the cap layer 42a contains AlN. The crystal structure of AlN is at least one of a group consisting of a cubic crystal and a hexagonal crystal. This allows the crystal orientation of the alloy layer 41a and the alloy layer 41b to be properly oriented. In addition, the alloy layer 41a and the alloy layer 41b can have a polycrystalline structure. This allows the deformability of the laminate 10 to be improved.
[0031] The cap layer 42a is disposed between the alloy layers 41a and 41b, thereby improving the crystallinity of the alloy layers 41a and 41b. As a result, crystal defects other than those at the grain boundaries in the alloy layers 41a and 41b can be reduced. As a result, the thermoelectric conversion efficiency of the laminate 10 and the sensitivity of the magnetic sensor can be further improved.
[0032] The thickness of the cap layer 42a is preferably 1 nm or more and 50 nm or less. When the thickness of the cap layer 42a is 2 nm or more, the crystallinity of the alloy layer 41a and the alloy layer 41b can be further improved. This can further improve the thermoelectric conversion efficiency of the laminate 10. The thickness of the cap layer 42a is more preferably 2 nm or more. On the other hand, when the thickness of the cap layer 42a is 5 nm or less, the deformability of the laminate 10 is further improved. The thickness of the cap layer 42a is more preferably 5 nm or less.
[0033] (Mixed layer 40b) As shown in FIG. 1, the mixed layer 40b is provided on the mixed layer 40a. The mixed layer 40b includes an alloy layer 41b and a cap layer 42b from the side closer to the buffer layer. The alloy layer 41b includes a magnetic material according to an embodiment of the present invention. The effect and preferred structure of the alloy layer 41a are similar to those of the magnetic material according to an embodiment of the present invention. The effect and preferred structure of the cap layer 42b are similar to those of the cap layer 42a.
[0034] The laminate 10 according to the present embodiment has the above-mentioned configuration. Next, the effects of the laminate 10 according to the present embodiment will be described. The laminate 10 according to the present embodiment has excellent deformability because a substrate having excellent deformability can be used. In addition, by sandwiching the alloy layer 41a and the alloy layer 41b between layers having insulating AlN, it is possible to easily control the crystal orientation of the alloy layer 41a and the alloy layer 41b and promote the improvement of the crystallinity. As a result, the laminate 10 exhibits a large anomalous Nernst effect (ANE) and anomalous Hall effect (AHE). Therefore, the laminate 10 according to the present embodiment has high thermoelectric conversion efficiency and high magnetic sensitivity.
[0035] The laminate 10 according to the present embodiment may have three or more mixed layers. There may be a diffusion region between the alloy layer and the cap layer or the buffer layer. The diffusion region has a composition intermediate between the alloy layer and the cap layer or the buffer layer. It is preferable that the diffusion region is substantially absent.
[0036] <Thermoelectric conversion element> Next, a thermoelectric conversion element 10a according to an embodiment of the present invention will be described with reference to the drawings. Note that, in cases where the same configuration is used, the same reference numerals will be used and the description will be omitted.
[0037] 3 is a schematic diagram of a thermoelectric conversion element 10a according to an embodiment of the present invention. As shown in FIG. 3, the thermoelectric conversion element 10a according to this embodiment has a thermoelectric conversion material 11 and an electrode material 12.
[0038] (Thermoelectric Materials 11) As shown in FIG. 3, the thermoelectric conversion material 11 has a sheet shape. The thermoelectric conversion material 11 is wound in a spiral shape. The thermoelectric conversion material 11 has a cylindrical shape as a whole. A temperature gradient occurs in the axial direction of the cylinder, and an electromotive force occurs in the circumferential direction of the cylinder. This causes thermoelectric conversion. In this embodiment, the thermoelectric conversion material 11 has a laminate according to an embodiment of the present invention. This allows the thermoelectric conversion material 11 to have large deformability and large thermoelectric conversion efficiency. The shape of the thermoelectric conversion material 11 is not particularly limited, and may be various shapes depending on the object or environment that generates the temperature gradient.
[0039] (electrode material 12) As shown in Fig. 3, the electrode material 12 is connected to both ends of the thermoelectric conversion material 11 wound in a spiral shape. This allows the electromotive force generated in the thermoelectric conversion material 11 to be used as an electric current. The electrode material 12 may be any material that is conductive. An example of a conductive material is a copper wire.
[0040] <Magnetic sensor> Next, a magnetic sensor 10b according to an embodiment of the present invention will be described with reference to the drawings. Note that, in cases where the same configuration is used, the same reference numerals will be used and the description will be omitted.
[0041] 4 is a schematic diagram showing a magnetic sensor 10b according to an embodiment of the present invention. As shown in FIG.
[0042] (Detection unit 13) The detection unit 13 detects a magnetic field. In this embodiment, the detection unit 13 has a laminate according to an embodiment of the present invention. This allows the detection unit 13 to have large deformability and high timing detection sensitivity.
[0043] <Method of manufacturing laminate> Next, a method for producing a laminate according to an embodiment of the present invention will be described. Fig. 5 shows a flow chart of the method for producing a laminate according to this embodiment. As shown in Fig. 5, the method for producing a laminate according to this embodiment has the following features. (a) Providing an AlN layer on a substrate (b) providing an alloy layer having a Co-based Heusler alloy on the AlN layer; (c) providing a cap layer comprising AlN on the alloy layer. (d) heat-treating the substrate provided with the cap layer at 400°C or more and 800°C or less
[0044] (Step of forming an AlN layer on the substrate) In the step of providing an AlN layer on a substrate, an AlN layer is provided on a flat surface of the substrate. The method of providing an AlN layer on a substrate may be a vapor phase growth method. Vapor phase growth methods include a method of nitrogen reactive sputtering on an Al target and a method of direct sputtering from an AlN target. In the case of nitrogen reactive sputtering on an Al target, a mixed gas of Ar and N2 may be used as a sputtering gas. In the case of direct sputtering from an AlN target, Ar gas may be used as a sputtering gas. The temperature of the substrate may be room temperature. Thermally oxidized Si, Al2O3, SiO2, Glass, and polyimide may be used as the substrate. It is preferable to use a substrate having deformability. It is also preferable to use a substrate having heat resistance. The thickness of the substrate to be used is not particularly limited, but the lower limit may be 50 nm or more, for example. The upper limit may be 1 mm, for example.
[0045] (Step of Providing an Alloy Layer Having a Co-Based Heusler Alloy on the AlN Layer) The method of providing an alloy layer having a Co-based Heusler alloy on the AlN layer may be a vapor deposition method. Vapor deposition methods include vacuum deposition and sputtering. The sputtering method may be DC sputtering from an alloy target or RF sputtering. The sputtering method may be co-sputtering from one or more sputtering targets. The vacuum deposition method may be co-evaporation. In the sputtering method, inert gas ions generated by discharge collide with a target, which is a solid raw material, to eject elements of the raw material. The ejected raw material elements are deposited on the AlN layer. This forms an alloy layer. In the vacuum deposition method, a Co-based Heusler alloy may be used as a raw material, or a single metal may be used as a raw material.
[0046] (Step of Providing a Cap Layer Having AlN on the Alloy Layer) In the step of providing a cap layer having AlN on the alloy layer, an AlN layer is provided on the alloy layer having a Co-based Heusler alloy. The method of providing an AlN layer on the alloy layer having a Co-based Heusler alloy may be a vapor phase growth method. Examples of the vapor phase growth method include a method of nitrogen reactive sputtering on an Al target and a method of direct sputtering from an AlN target. In the case of nitrogen reactive sputtering on an Al target, a mixed gas of Ar and N2 may be used as a sputtering gas. In the case of direct sputtering from an AlN target, Ar gas may be used as a sputtering gas. The method of providing a cap layer having AlN on the alloy layer may be the same as the method of providing an AlN layer on a substrate.
[0047] (A process of heat treating the substrate provided with the cap layer at 400°C to 800°C) A laminate obtained by providing a buffer layer, an alloy layer, and a cap layer on a substrate is heat-treated at 400°C to 800°C. As a result, the Co-based Heusler alloy in the alloy layer becomes polycrystalline. The crystal orientation of the Co-based Heusler alloy in the alloy layer is oriented in the thickness direction of the laminate. Furthermore, the crystal structure of the Co-based Heusler alloy in the alloy layer becomes at least one type selected from the group consisting of an L21 ordered structure and a B2 ordered structure.
[0048] If the heat treatment temperature is less than 400°C, the crystal structure of the Co-based Heusler alloy in the alloy layer may not be at least one of the L21 ordered structure and the B2 ordered structure. The heat treatment temperature is preferably 430°C or more, more preferably 480°C or more. On the other hand, if the heat treatment temperature is more than 800°C, the crystal structure of the Co-based Heusler alloy in the alloy layer may not be at least one of the L21 ordered structure and the B2 ordered structure. In addition, the Co-based Heusler alloy in the alloy layer may not be polycrystalline. The heat treatment temperature is preferably 650°C or less, more preferably 550°C or less. Here, the heat treatment temperature refers to the temperature of the laminate.
[0049] The pressure of the heat treatment is not particularly limited as long as the crystal structure of the Co-based Heusler alloy in the alloy layer is at least one of the group consisting of the L21 ordered structure and the B2 ordered structure. -4 The pressure of the heat treatment may be 10 Pa or less. The pressure of the heat treatment is not particularly limited as long as the crystal structure of the Co-based Heusler alloy in the alloy layer is at least one selected from the group consisting of the L21 ordered structure and the B2 ordered structure. The pressure of the heat treatment may be 2 hours or more.
[0050] When two or more alloy layers are provided in the laminate, a cap layer having AlN may be provided on the alloy layer, and then another alloy layer and cap layer may be provided on the cap layer. The method of providing the alloy layer and cap layer may be the same as the above-mentioned method. EXAMPLES
[0051] The effects of the present invention will be explained in more detail below with reference to examples. The conditions in the examples are merely examples of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these examples. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.
[0052] In the embodiment, thermally oxidized Si was used as the substrate. First, a buffer layer of AlN was provided on the substrate by performing nitrogen reactive sputtering on an Al target. The target was Al metal, the atmosphere was a mixed gas of Ar and N2, and the film formation temperature was room temperature. Then, a Co2MnGa (CMG) alloy layer was provided on the buffer layer by performing DC sputtering from an alloy target. The target was a Co2MnGa alloy, the atmosphere was Ar gas, and the film formation temperature was room temperature. After that, an alloy layer and a cap layer were further provided. As a result, the mixed layer having the alloy layer and the cap layer was a total of two layers. The obtained laminate was subjected to a heat treatment at a temperature of 500°C, a heat treatment time of 3 hours, and a heat treatment pressure of 10 -4 The heat treatment was carried out at a temperature of 0.1 Pa or less.
[0053] A number of stacks were produced by varying the thickness of the alloy layer. The alloy layer of Example 1 had a thickness of 2.5 nm. The alloy layer of Example 2 had a thickness of 5.0 nm. The alloy layer of Example 3 had a thickness of 12.5 nm. The alloy layer of Example 4 had a thickness of 25.0 nm. The cap layer of Examples 1 to 4 had a thickness of 5 nm. The buffer layer of Examples 1 to 4 had a thickness of 10 nm or more.
[0054] The thickness direction and horizontal cross section of the obtained laminate were observed by a transmission electron microscope (SEM). FIG. 6 shows a TEM photograph of the laminate according to the embodiment of the present invention. As shown in FIG. 6, the laminate according to the embodiment has a thermally oxidized Si substrate and an AlN buffer layer, and further has a total of two mixed layers having a Co2MnGa alloy layer and an AlN cap layer. The interfaces of the layers were steep. It was observed that there was no noticeable interdiffusion between the layers. It was also observed that the Co2MnGa (CMG) alloy layer had polycrystals.
[0055] The crystal structure of each layer of the laminate was examined by X-ray diffraction (XRD). FIG. 7 shows the results of X-ray diffraction measurement of the laminate according to the embodiment of the present invention. As shown in FIG. 7, a strong diffraction peak was observed in the (220) plane of CMG. In other words, it was observed that the Co2MnGa (CMG) alloy layer had a crystalline structure rather than an amorphous structure. It was also observed that the (110) plane of the Co2MnGa (CMG) alloy was oriented perpendicular to the thickness direction of the laminate. Furthermore, Example 3, in which the thickness of the alloy layer was 12.5 nm, had the sharpest diffraction peak in the (220) plane.
[0056] As shown in Figure 7, a strong diffraction peak was observed in the (002) plane of AlN. In other words, it was observed that the (001) plane of AlN in the AlN buffer layer and cap layer was oriented perpendicular to the thickness direction of the stack. In addition, the (001) plane of AlN had a crystal orientation relationship parallel to the (110) plane of the Co2MnGa (CMG) alloy.
[0057] The surface roughness of the alloy layer of the obtained laminate was measured by X-ray reflectometry (XRR). FIG. 8 shows the measurement result of the X-ray reflectivity of the laminate of the embodiment of the present invention. Also, for comparison, the measurement result of the laminate before heat treatment by X-ray reflectometry is shown. As shown in FIG. 8, the surface roughness of the alloy layer of the laminate of the embodiment of the present invention was Ra 0.31 nm. This confirmed that the surface roughness of the alloy layer of the laminate of this embodiment was low. In addition, the surface roughness of the alloy layer before heat treatment of the laminate was Ra 0.85 nm. In other words, it was observed that a solid laminate structure was formed by the heat treatment.
[0058] The anomalous Nernst effect of the obtained laminate was evaluated. The anomalous Nernst effect was measured by sweeping a magnetic field perpendicular to the laminate while applying a temperature gradient in the in-plane direction of the laminate, and measuring the anomalous Nernst voltage generated in a direction perpendicular to both the temperature gradient and the magnetic field. FIG. 9 shows the measurement results of the anomalous Nernst effect of the laminate according to the embodiment of the present invention. As shown in FIG. 9, an anomalous Nernst coefficient of 2.5 μV / K or more was measured in this embodiment. Also, an anomalous Nernst coefficient of up to 5 μV / K was measured. In other words, it was found that this embodiment has high thermoelectric conversion efficiency.
[0059] The anomalous Hall effect of the obtained laminate was evaluated. The anomalous Hall effect was measured by passing a current through the laminate, applying a magnetic field in a direction perpendicular to the current, and measuring the Hall electromotive force in a direction perpendicular to the current and magnetic field. FIG. 10 shows the measurement results of the anomalous Hall effect of the laminate according to the embodiment of the present invention. As shown in FIG. 10, the laminate according to this embodiment showed a large anomalous Hall effect of 5% or more. Furthermore, it showed a large anomalous Hall effect of up to 7.5%. In other words, this embodiment has high magnetic sensitivity.
[0060] A cross section parallel to the thickness of the obtained laminate was observed with a transmission electron microscope (TEM). Fig. 11 shows a TEM photograph of the laminate according to the embodiment of the present invention. As shown in Fig. 11, it was observed that the crystal orientation of the Co2MnGa (CMG) alloy layer was oriented in the thickness direction of the laminate. It was also observed that the Co2MnGa (CMG) alloy layer was polycrystalline.
[0061] Therefore, since the laminate according to this embodiment is polycrystalline, it has high deformability compared to a single crystal thin film. In addition, the Co2MnGa(CMG) alloy layer has a crystalline structure rather than an amorphous structure. This allows the Co2MnGa(CMG) alloy to have a topological electronic band structure. In addition, the crystal orientation of the Co2MnGa(CMG) alloy layer is oriented in the thickness direction of the laminate. Therefore, the laminate according to this embodiment exhibits a high anomalous Nernst coefficient and a high anomalous Hall angle. In other words, it was confirmed that the laminate according to this embodiment has a high thermoelectric conversion efficiency and a high magnetic sensitivity.
[0062] Figure 12 shows the measurement results of the anomalous Nernst voltage when the magnetic material according to the embodiment of the present invention is formed on a flexible substrate. As shown in Figure 12, the magnetic material according to the embodiment of the present invention on a flexible substrate has a large anomalous Nernst coefficient of about 4 μV / K. A polyimide substrate was used as the flexible substrate.
[0063] 13 is a photograph of a laminate in which the magnetic material according to the embodiment of the present invention is formed on a polyimide substrate. As shown in FIG. 13, the laminate according to the embodiment of the present invention has high flexibility.
[0064] Throughout the specification, when a part is described as "having" or "comprising" a certain element, this does not mean excluding other elements, but may further include other elements, unless specifically stated to the contrary.
[0065] In addition, the terms "... unit" and "... step" used in the specification refer to a unit that processes at least one function or operation, which may be embodied as hardware or software, or a combination of hardware and software.
[0066] In addition, within the scope of the invention, the components in the above-described embodiments may be replaced with well-known components, and the above-described modified examples may be combined as appropriate. [Industrial Applicability]
[0067] As described above, according to the present invention, it is possible to provide a magnetic material, a laminate, and a method for manufacturing a laminate, which can be fabricated on a non-single crystal substrate or a flexible substrate and have excellent thermoelectric conversion efficiency, as well as a thermoelectric conversion element and a magnetic sensor having the laminate, and thus the present invention has high industrial utility. [Explanation of symbols]
[0068] 10 Laminate 10a Thermoelectric conversion element 10b Magnetic sensor 12 Electrode materials 13 Detection section 20 Base material 30 Buffer layer 40a, 40b mixed layer 41a, 41b alloy layer 42a, 42b cap layer
Claims
1. A substrate, a buffer layer provided on the substrate, the buffer layer having AlN, the crystal structure of the AlN being at least one selected from the group consisting of cubic and hexagonal crystals; The buffer layer is provided on the buffer layer, and the buffer layer is provided on the buffer layer from a side closer to the buffer layer. an alloy layer including a magnetic material; A cap layer having AlN, the crystal structure of the AlN being at least one selected from the group consisting of cubic and hexagonal crystals; and a mixed layer having the cap layer. the magnetic material has a polycrystalline Co-based Heusler alloy and is in the form of a film; The crystal structure of the Co-based Heusler alloy is L2 1 At least one selected from the group consisting of an ordered structure and a B2 structure; The crystal orientation of the Co-based Heusler alloy is oriented in the thickness direction of the film. A laminate comprising:
2. The chemical composition of the magnetic material is represented by the formula: Co α Mn β X γ It is expressed as X is at least one selected from the group consisting of Ga, Al, Si, and Ge; α is in the range of 1.8 to 2.2, β is in the range of 0.8 to 1.2, and γ is in the range of 0.8 to 1.
2. The laminate according to claim 1 .
3. In the magnetic material, the half-width of the X-ray diffraction peak of the crystal orientation of the Co-based Heusler alloy oriented in the thickness direction of the film is 1° or less.
3. The laminate according to claim 1 or 2.
4. In the magnetic material, the thickness of the film is 2 nm or more and 50 nm or less. The laminate according to any one of claims 1 to 3.
5. On the mixed layer, one or more layers of the mixed layer are further provided. The laminate according to any one of claims 1 to 4.
6. The thickness of the buffer layer is 10 nm or more and 50 nm or less, and the thickness of the cap layer is 1 nm or more and 50 nm or less. The laminate according to any one of claims 1 to 5.
7. A thermoelectric conversion material having the laminate according to any one of claims 1 to 6 and an electrode material. A thermoelectric conversion element comprising:
8. A detector for detecting magnetism comprising the laminate according to any one of claims 1 to 6. A magnetic sensor comprising:
9. A method for producing the laminate according to any one of claims 1 to 6, comprising the steps of: Providing an AlN layer on a substrate; providing an alloy layer having a Co-based Heusler alloy on the AlN layer; providing a cap layer comprising AlN on the alloy layer; and heat treating the base material on which the cap layer is provided at a temperature of 400° C. or more and 800° C. or less. A method for producing a laminate comprising the steps of:
10. In the heat treatment step, the pressure is 10 -4 Pa or less, and the heat treatment time is 2 hours or more. The method for producing a laminate according to claim 9 .
Citation Information
Patent Citations
Magnetoresistive film with high electrical resistivity
JP2001094175A
Surface direct electrification giant magnetoresistance element lamination film, surface direct electrification giant magnetoresistance element, and application of the same
JP2019033106A
Electronic element, method of manufacturing the same, and magnetoresistive element
JP2020043165A
Thermoelectric conversion device and thermoelectric conversion element
JP6611167B2
Magnetoresistance effect element
WO2018159138A1